Penerapan Prinsip Syariah dalam Produk Pembiayaan: Studi Kasus pada Lembaga Pembiayaan Syariah di Indonesia - Siti Itsna Syamsiyah; Vina Maratus Salsabila; Putri Shinta Dewi; Mashudi Mashudi; Qomarul Huda (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the extent to which Sharia principles are implemented in financing products by Islamic financial institutions in Indonesia, with a focus on a case study of Bank Syariah Indonesia (BSI). This research employs a qualitative method with a literature study approach. The findings indicate that although financing products such as murabahah, ijarah, musyarakah, and mudharabah are theoretically designed in accordance with Sharia principles, in practice there are still deviations, particularly in procedural aspects and the execution of contracts (akad). One of the analyzed cases reveals an asset auction process involving a customer's collateral that is considered inconsistent with the principles of justice, deliberation (musyawarah), and transparency. This highlights the need for a comprehensive reinforcement of Sharia principles implementation—not only in product design but also in operational procedures and dispute resolution mechanisms. The study recommends enhancing Sharia literacy, evaluating internal standard operating procedures (SOPs), and ensuring more active supervision by the Sharia Supervisory Board to ensure that Islamic principles are genuinely embodied in the practices of Islamic finance in Indonesia.